ANALISIS MANAJEMEN BISNIS SYARIAH PENGARUH PROMOSI FLASH SALE DI APLIKASI E-COMMERCE SHOPEE TERHADAP PERILAKU KONSUMTIF MASYARAKAT KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT - Heryanti, Riani; Thantawi, Tubagus Rifqy; Suryani, Ermi (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
This study aims to analyze and explain the variable Flash Sale Promotion in the E-commerce Shopee Application that has a partial or simultaneous effect on the consumptive behavior of the people of Pamijahan District from a Shariah Business Management perspective. The research method used is a quantitative method with simple linear analysis using SPSS Version 25 and Microsoft Excel, and data collection using questionnaires and Google forms with Likert scale measurements. The research sample used the Isaac and Michael formula with a total sample of 348 respondents, namely the people of Pamijahan District. The results of this study are Flash Sale Promotion in the Shopee E-commerce Application which has a partial positive effect on the Consumptive Behavior of the Pamjjahan District Community in a Shariah Business Management Perspective.